Sirkumsisi Perempuan dalam Islam (Studi Komparatif Fatwa MUI dan Dar Al-Ifta’ Mesir) - Fashihuddin, Muhammad (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The proposition of female circumcision has become a protracted public polemic in many parts of the world. The polemic arose due to the doctrine of tradition, or it recognizes in the Shari’a until it appoints to the fatwa institution for the legal stipulation. However, there are two contradictory fatwas, namely in Indonesia (MUI) and Egypt (Dār al-Iftā”), which are appropriate to reveal the reasons behind the two different sides in those fatwas. This study aims to explore the background of the enactment of the fatwa and uncover the legal arguments built on it. The type of study used is normative qualitative research with a comparative approach. The results found include: First, the MUI fatwa was determined based on the submission of a fatwa by Indonesian government agencies on the issue of rejecting the practice of circumcision by some people. Nevertheless, the fatwa of Dār al-Iftā” was determined based on the ambiguity of the fatwa by the muftis of Egypt. Second, the MUI fatwa states that female circumcision is part of the Shari’a based on the verse of the Qur’an and hadith. For the time being, Dār al-Iftā” forbids the practice of circumcision by denying the validity of the hadith about of it through fuqaha vows and fatwas. Masalah sirkumsisi perempuan telah menjadi polemik publik yang berkepanjangan di belahan dunia. Polemik tersebut muncul sebab doktrinasi tradisi atau memang diakui dalam syariat hingga diangkat pada lembaga fatwa untuk ditetapkan hukumnya. Namun, muncul fatwa di Indonesia (MUI) dan Mesir (Dār al-Iftā‟) yang saling bertolak belakang, sehingga layak untuk diungkap alasan dibalik perbedaan fatwa tersebut. Penelitian ini bertujuan untuk menggali latar belakang atas ditetapkannya fatwa dan mengungkap argumen-argumen hukum yang dibangun di dalamnya. Jenis penelitian yang digunakan adalah penelitian kualitatif normatif dengan pendekatan komparatif. Hasil yang ditemukan meliputi: Pertama, fatwa MUI ditetapkan atas dasar pengajuan fatwa oleh instansi pemerintah Indonesia atas isu penolakan praktik sirkumsisi oleh sebagian masyarakat. Sementara fatwa Dār al-Iftā’ ditetapkan atas dasar ambiguitas fatwa oleh para mufti Mesir. Kedua, fatwa MUI menyatakan sirkumsisi perempuan termasuk bagian dari syariat yang berlandas pada dalil al-Qur’an dan hadis. Sementara Dār al-Iftā’ menyatakan haram praktik tersebut dengan menyangkal keabsahan hadis-hadis sirkumsisi melalui kaul fukaha dan fatwa.